Antimicrobial Susceptibility and Virulence of mcr-1-Positive Enterobacteriaceae in China, a Multicenter Longitudinal Epidemiological Study - Jiang, Bin; Du, Pengcheng; Jia, Peiyao; Liu, Enbo; Kudinha, Timothy; Zhang, Hui; Li, Dongxue; Xu, Yingchun; Xie, Liangyi; Yang, Qiwen (Frontiers in Microbiology, 2020)
This study was to investigate the prevalence of mcr-1 positive Enterobacteriaceace (MPE) in intra-abdominal infections (IAIs), urinary tract infections (UTIs) and lower respiratory tract infections (LRTIs) in China. A total of 6,401 Enterobacteriaceae isolates were collected consecutively from IAI, UTI and LRTI patients in 19 hospitals across mainland China during 2014-2016. MPE isolates were screened by PCR detection for mcr gene. The resistance profiles were tested by antimicrobial susceptibility test. All MPE isolates were characterized by Pulse Field Gel Electrophoresis, Multilocus-sequence typing, O and H serotyping and whole genome sequencing. Among the 6,401 Enterobacteriaceae isolates, 17 E. coli strains (0.27%) were positive for mcr-1 gene. MPE prevalence rate in IAI, UTI and LRTI patients was 0.34% (12/3502), 0.23% (5/2154) and 0% (0/745), respectively. The minimum inhibition concentration (MICs) of colistin against 3 isolates were of 0.5-2 mg/L, and 4-8mg/L against other 14 isolates. All the 17 isolates were susceptible to meropenem, imipenem, tigecycline and ceftazidime/avibactam. The 17 MPE isolates belonged to 14 different ST types, and those belonged to the same STs were not clonal by PFGE. The mcr-1 harboring plasmid of 10 MPE isolates could transfer to the recipients by conjugation and the colistin MICs of the transconjugants were ranged from 0.5 to 8 mg/L. Mcr-1-carrying plasmids from the 17 MPE isolates could be grouped into four clusters, including 8 IncX4 type, 4 IncI2 type, 4 IncHI2A type and 1 p0111 type. Multiple drug resistance genes and virulence genes were detected. In conclusion, the prevalence of MPE in IAI, UTI and LRTI were low in China, and no clonal transmission was identified in our study. Most MPE isolates exhibited low level colistin resistance. However, our study indicated that MPE isolates always carried a variety of drug resistance and virulence genes, which should be paid more attention.